Navigating the Abyss: Artworks Born from Turbulent Minds, Depression, and Aspirations by the Patterns of the Sea - Ismail, K. Asril; Abdden, Azme Zanal (UPT Pusat Penerbitan LP2MPP ISI Bali, 2023)
This academic enquiry explores the profound connection between the human psyche, depression, and the inexhaustible wellspring of creativity that emerges from the depths of turmoil. It delves into the world of artistry conceived amidst the turbulence of the mind, and how the patterns found in the sea serve as a poignant metaphor for the journey through emotional tempests. Art has long been a powerful channel for expressing the complexity of human emotions, and this paper sheds light on how melancholy, often seen as a debilitating force, can paradoxically become a wellspring of artistic inspiration. Through various mediums, artists have channeled their inner struggles into evocative and thought-provoking works that invite viewers to contemplate the enigmatic relationship between darkness and creativity. Drawing parallels with the patterns found in the sea, which can range from the gentle ripples of calm waters to the violent crashes of waves, this underscores the idea that the human mind, like the ocean, is ever-changing and dynamic. Just as the sea's turbulent nature can give rise to awe-inspiring beauty, so too can the tumultuous currents of the mind lead to the creation of captivating and transformative artworks. This exploration serves as a reminder of the resilience of the human spirit and its ability to find solace, meaning, and inspiration even in the darkest of moments. The artworks born from the depths of depression and nurtured by the aspirational yearning for tranquility exemplify the indomitable human capacity to transform adversity into works of enduring beauty, inviting audiences to navigate their own emotional abyss and discover the potential for creativity and healing within. The primary purpose is to gain a deeper understanding of how individuals dealing with melancholic episodes use art as a means of expressing their emotions. By analysing sketches created by the author himself, the reflective manner aims to uncover the nuances embedded in the artwork, shedding light on the ways in which depression influences their creative output. Utilising poetic inquiry as an engagement method is an approach that combines artistic expression, often in the form of poetry, with the research process. This method allows the exploration and engage with topics in a creative and subjective way, fostering deeper insights and connection with both the subject matter and the readers. Sketches created exhibited a higher prevalence of turbulent patterns and expressions of distress. The presence of sea patterns served as a bridge between their internal emotional landscapes and the external world, allowing for a profound form of communication and catharsis. In the fusion of poetic inquiry, the mesmerising us on performing art such as the Silat performance, and the inspiration drawn from the sea, the areas in uncovering a symphony of artistry and expression transcends boundaries in the norms on academic inquiry, revealing the profound essence of understanding in the questions explored, stories shared, and movements that propel much like the movements like the eternal sea.